2021
DOI: 10.1038/s41419-021-03772-y
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine aggravates vascular adiponectin resistance via ubiquitin-mediated adiponectin receptor degradation in diabetic Apolipoprotein E knockout mouse

Abstract: There is limited and discordant evidence on the role of nicotine in diabetic vascular disease. Exacerbated endothelial cell dysregulation in smokers with diabetes is associated with the disrupted adipose function. Adipokines possess vascular protective, anti-inflammatory, and anti-diabetic properties. However, whether and how nicotine primes and aggravates diabetic vascular disorders remain uncertain. In this study, we evaluated the alteration of adiponectin (APN) level in high-fat diet (HFD) mice with nicotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…The blood of smokers typically exhibits impaired antioxidant capacity and an increase in oxidized lipids. Nicotine, a significant component of e-cigarettes and cigarettes, triggers vascular APN resistance and diabetic endothelial dysfunction through socs3-mediated degradation of AdipoR1 ubiquitination [ 149 ]. Cigarette smoke, in turn, exacerbates diabetic vascular fibrosis and induces eNOS uncoupling, enhancing aortic Nox2 and Nox4 expression, which leads to the dysregulation of vascular tone [ 150 ].…”
Section: Effect Of Targeting Oxidative Stress In Diabetes-induced End...mentioning
confidence: 99%
“…The blood of smokers typically exhibits impaired antioxidant capacity and an increase in oxidized lipids. Nicotine, a significant component of e-cigarettes and cigarettes, triggers vascular APN resistance and diabetic endothelial dysfunction through socs3-mediated degradation of AdipoR1 ubiquitination [ 149 ]. Cigarette smoke, in turn, exacerbates diabetic vascular fibrosis and induces eNOS uncoupling, enhancing aortic Nox2 and Nox4 expression, which leads to the dysregulation of vascular tone [ 150 ].…”
Section: Effect Of Targeting Oxidative Stress In Diabetes-induced End...mentioning
confidence: 99%
“…Therefore, to study the cardiac effects of e-cigarettes, we used a relevant model with a reliable phenotype, wild-type mouse model on HFD 19 . In the cardiovascular system, the synergistic effect of HFD and nicotine have been studied by our and other groups 1 , 37 . Using the HFD mice model to study synergistic factors that increase morbidity or mortality in obese people who vape has relevance to the vaping company's young target population and the health of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Mineur et al [54] nicotine was injected via IP once a day per 30 days and only males C57Bl/6 mice were used. In ApoE -/- mice, Gao et al [55] exposed mice to nicotine via osmotic minipumps for 12 weeks and observed an inhibition of body weight gain induced by HFD. Animal sex for this study was not disclosed.…”
Section: Discussionmentioning
confidence: 99%